Analisis Manajemen Risiko Dan Strategi Mitigasi Usaha Pada UMKM Buket Jurnalis Di Kota Bandung - Nabila Zulfa Azizah; Chika Putri Irwanda; Nira Destiani Dewi; Nurul Laily Oktaviana; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
UMKM Buket Jurnalis is a small business engaged in selling artificial flower bouquets, fresh flowers, and supporting products such as gift boxes and standing flowers. Established in late 2021, the business has grown gradually in response to market demand. This study aims to identify and analyze the various risks faced by UMKM Buket Jurnalis and to determine appropriate mitigation strategies to ensure business continuity. The research method used is a qualitative descriptive approach with a case study through direct interviews with the business owner. The findings indicate that UMKM Buket Jurnalis faces six main categories of risk: market, financial, marketing, operational, human resources, and legal risks. The most significant risks include fluctuating seasonal demand, rising raw material costs, and limited workforce capacity during peak periods. The mitigation strategies applied involve quality control, market price evaluation, customer service improvement, inventory There are no sources in the current document.anagement, and employee training. By implementing effective risk management practices, UMKM Buket Jurnalis is expected to enhance its competitiveness and maintain sustainable business performance within the increasingly competitive florist industry.